2003
DOI: 10.1007/s00421-002-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of titin in strength and power athletes

Abstract: The purpose of this investigation was to identify characteristics of the muscle protein titin in different athletic populations with increased levels of strength and power relative to non-athletes. Subjects fell into one of four groups: (1) non-athletes (NA) ( n=5), (2) weightlifters (WL) (n=5), (3) powerlifters (PL) (n=5), (4) sprinters (S) (n=5). A one repetition maximum in the squat exercise was performed to assess strength. In addition, countermovement vertical jump trials were performed to assess power ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
3
17
0
5
Order By: Relevance
“…Although measuring the absolute content of connectin within fibers is difficult due to its large molecular mass, its isoform composition (α:β) has been thought to be an indicator for the protein metabolism of connectin [20,21,30]. It has been shown that the relative content of β-connectin (β/α+β) is larger in fast type II fibers than in slow type I fibers [30], and the smaller β/α+β may provide larger passive resistance to stretch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although measuring the absolute content of connectin within fibers is difficult due to its large molecular mass, its isoform composition (α:β) has been thought to be an indicator for the protein metabolism of connectin [20,21,30]. It has been shown that the relative content of β-connectin (β/α+β) is larger in fast type II fibers than in slow type I fibers [30], and the smaller β/α+β may provide larger passive resistance to stretch.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationship between resistance training and connectin isoform composition in human muscle. Although it has been shown that, in humans, exercise training did not cause a considerable change in the muscle connectin isoform composition [20], it has also been shown that β-connectin isoform percentage tends to be lower in competitive athletes than in non-athletes [21]. Therefore, a prolonged period of strenuous exercise training may cause any change in β-connectin, thereby affecting joint stiffness.…”
mentioning
confidence: 96%
“…Moritani and deVries (1979) have demonstrated that in high intensity strength training the neural factors dominate in strength development at the three first weeks of training, while the hypertrophic factors start to play a major role after this time. In power training, increases in muscle power capabilities have been observed with coincidental changes in neural factors ; however, possible muscle structural adaptations have not been clearly identified (Ha¨kkinen et al, 1985;McBride et al, 2003;McGuigan et al, 2003).…”
mentioning
confidence: 99%
“…While myosin is directly involved in the force production processes of muscle contraction, titin, which is a large protein acting as anchor between the z-lines and myosin within the sarcomere, is thought to have effects on the elastic characteristics of muscle fibers (Tskhovrebova & Trinick, 2002). It is possible that improvements in muscle power could be related to shifts in MHC or titin isoforms, because both of them contribute to the force production (Staron et al, 1990;McBride et al, 2003). Andersen and Aagaard (2000) have shown that the 3 months of heavy resistance training decreases the amount of MHC IIX content, while MHC IIA content increases.…”
mentioning
confidence: 99%
“…Sarcomeres that are exposed to greater strains may express titins with larger elastic segments. In fact, sprinters expressed a greater percentage of titin-1 isoforms than non-athletes [22]. It is possible that the titin is capable of storing and releasing elastic energy [18], and consequently, RSHS could be reduced.…”
Section: Discussionmentioning
confidence: 99%